The Role of AI In Creating Competitive Advantage For Small E-Commerce Businesses - Jain, Satvik (Journal of Neonatal Surgery, 2025)
The rapid advancements in Artificial Intelligence (AI) are reshaping the e-commerce landscape, offering unprecedented opportunities for small businesses to gain a competitive edge. This research explores the pivotal role of AI in enhancing the competitiveness of small e-commerce enterprises through improved personalization, operational efficiency, and targeted marketing strategies. Key findings highlight the transformative impact of AI-driven technologies such as chatbots, predictive analytics, and inventory optimization, which empower small businesses to deliver enhanced customer experiences, optimize resources, and compete with larger players. Despite the significant benefits, barriers such as cost, technical expertise, and data limitations persist. The study proposes strategies to overcome these challenges, including leveraging affordable AI tools, partnerships, and open-source platforms. The insights derived from this research provide actionable recommendations for small e-commerce businesses to harness AI effectively, paving the way for sustainable growth in a competitive market.